ANALYSIS OF LIGTHING WITH EYE IN TAILOR WORKERS AT PAJAK HORAS PEMATANG SIANTAR IN 2023 - Herlina Jamaluddin EL- Matury (Jurnal Penelitian Kesmasy, 2023)
Based on the Minister of Manpower, RI No. 05 of 2018 concerning occupational safety and health in the work environment, the standard lighting level for sewing work is 200 lux. Fatigue that is less than 200 lux can slow down work and result in work fatigue, especially eye fatigue, many complaints or symptoms due to eye fatigue complaints, namely headaches, loss of concentration, decreased opportunity to think and intellectual abilities. Eye fatigue is eye strain caused by the use of the sense of sight when working which requires the ability to see for a long time and is usually accompanied by uncomfortable viewing conditions, due to eye fatigue. The method of this research used a descriptive method with a cross-sectional design. The population of this research was 30 and the samples were selected using total sampling. Research data was obtained with a questionnaire instrument. Data analysis was performed univariately and bivariately using chi square. The results showed that there were 17 respondents (56.7%) who had a sewing room with abnormal lighting. there is a relationship between lighting and eye fatigue (p=0.001).